2018
DOI: 10.1016/j.jacc.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Tricuspid Valve Interventions

Abstract: Tricuspid regurgitation is a common finding in patients with left-sided valvular or myocardial disease, often being a marker for late-stage chronic heart failure with a grim prognosis. However, isolated tricuspid valve surgery remains infrequent and is associated with the highest mortality among all valve procedures. Hence, a largely unmet clinical need exists for less invasive therapeutic options in these patients. In recent times, multiple percutaneous therapies have been developed for treating severe tricus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(93 citation statements)
references
References 69 publications
0
92
0
1
Order By: Relevance
“…Future studies are required to better understand which patients are ideal candidates for percutaneous annuloplasty. Patients with leaflet tethering, organic degeneration of the leaflets and TR secondary to partial interference of pacemaker leads are unlikely to derive significant benefit from an annuloplasty strategy ( 16 18 ). Echocardiographic predictors are required to discern those who will benefit the most from percutaneous annuloplasty.…”
Section: Which Device For Which Patient? Moving Toward a Tailored Appmentioning
confidence: 99%
“…Future studies are required to better understand which patients are ideal candidates for percutaneous annuloplasty. Patients with leaflet tethering, organic degeneration of the leaflets and TR secondary to partial interference of pacemaker leads are unlikely to derive significant benefit from an annuloplasty strategy ( 16 18 ). Echocardiographic predictors are required to discern those who will benefit the most from percutaneous annuloplasty.…”
Section: Which Device For Which Patient? Moving Toward a Tailored Appmentioning
confidence: 99%
“…The latter may indeed lead to an undertreated population with end-stage right heart failure, usually linked with hepatic congestion and/or late-stage kidney disease ( 3 , 4 ). As a result, the management of isolated TR represents an unmet clinical need that has led to the development of transcatheter tricuspid valve intervention (TTVI) ( 5 ). TTVI can be classified according to their mechanism of action as follows: annuloplasty devices, caval stent devices, tricuspid valve (TV) replacement, and coaptation devices.…”
Section: Introductionmentioning
confidence: 99%
“…TTVI can be classified according to their mechanism of action as follows: annuloplasty devices, caval stent devices, tricuspid valve (TV) replacement, and coaptation devices. The initial experience with these first-generation transcatheter systems showed that despite the high-risk profile of TR patients undergoing TTVI, the majority of the procedures were well-tolerated with low in-hospital mortality rates (lower than surgical series) ( 5 ). Among them, coaptation devices attempt to increase valve coaptation by leaflet plication or occupying the regurgitant orifice with a spacer.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several transcatheter therapies are currently in early clinical testing as an alternative treatment option for severe TR in elderly patients at high or prohibitive surgical risk and persisting symptoms of right heart failure despite optimal medical therapy. 5 Malnutrition and impairment of hepatic or renal function may complicate the clinical course of patients currently evaluated for transcatheter tricuspid valve therapies. However, the prevalence and clinical relevance of malnutrition as well as periprocedural changes in nutritional status or hepatorenal function in these patients have to date not been studied.…”
Section: Introductionmentioning
confidence: 99%